ChemInform Abstract: Group 2 Catalysis for the Atom‐Efficient Synthesis of Imidazolidine and Thiazolidine Derivatives. Issue 49 (December 2015) - Arrowsmith, Merle; Hill, Michael S.; Kociok‐Koehn, Gabriele
Abstract: Among 3 alkaline earth bis(amide) precatalysts tested (M: Sr, Mg, Ca), the strontium compound is the most effective one.